Neutrophil-Lymphocyte Ratio(NLR), Platelet-Lymphocyte Ratio (PLR) and D-Dimer to Length of Stay in ICU of Pregnancy with COVID-19 Complicating Severe Coagulopathy - Mona Galatia Marpaung; Rizky Syahriar Syoufana; Radith Aulia; Julian Dewantiningrum (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2022)
Objective: The aim of this study was to obtain data that D-Dimer levels, Neutrophil-Lymphocyte Ratio (NLR), Platelet-Lymphocyte Ratio (PLR) as a prognostic factors of length of stay in ICU. The longer length of stay in the Intensive Care Unit (ICU) as an indicator of severe coagulopathy.Methods :This study uses an analytic observational study with a cross sectional approach to analyze NLR , PLR ,and the D-Dimer levels and their relationship to length of stay in ICU of pregnant women with COVID-19 infection who were treated at RSUP Dr. Kariadi during March 2020 to October 2021. Medical records of patients with pregnancy confirmed COVID-19 who were diagnosed by PCR (polymerase chain reaction) and treated at Dr Kariadi Hospital between March 2020 and October 2021 were reviewed, p value <0.05 considered significant. Results: The mean value of D-Dimer was 3746.6 ± 4852.33 (460-20) ug/L, NLR was 8.14 ± 6.35 (2.20-29.60), PLR was 27.66 ± 20.60 (6.80-96.66). 15 were treated in ICU with Length of stay 0.3 ± 0.46 (0-1) with the significancy was NLR p 0.008, PLR p 0.073 and D-dimer p 0.225. Conclusion : High NLR, PLR and D-dimer levels correlated with severe coagulopathy that effect the length of stay in ICU.Neutrophyl-Lymphocyte Ratio (NLR) , Platelet-Lymphocyte Ratio (PLR) dan D-dimer Terhadap Lama Rawat Inap di ICU pada Kehamilan dengan COVID-19 yang Mengalami Koagulopati Berat Abstrak Tujuan: Tujuan dari studi ini untuk menilai jumlah D-Dimer , Neutrophyl-Lymphocyte Ratio (NLR), Platelet-Lymphocyte Ratio (PLR) sebagai factor prognostic dari lama rawat inap di ICU. Metode: Studi ini menggunakan desain analitik observasional dengan pendekatan cross sectional untuk menganalisa NLR, PLR dan jumlah D Dimer dan hubungannya dengan lama rawat inap di ICU dari Wanita hamil dengan infeksi COVID 19 yang dirawat di RSUP Dr Kariadi selama bulan Maret 2020 hingga Oktober 2021, nilai p <0.05 dianggap signifikan. Hasil: Rerata nilai D Dimer dari subjek ialah 3746,6 ± 4852.33 (460-20) ug/L, NLR 8.14 ± 6.35 (2.20-29.60), PLR 27.66 ± 20.60 (6.80-96.66). 15 pasien dirawat di ICU dengan lama rawat inap 0.3 ± 0.46 (0-1) dengan nilai signifikansi dari NLR p 0.008, PLR p 0.073 dan D-dimer p 0.225. Kesimpulan: NLR dan D dimer yang tinggi berhubungan dengan keparahan koagulopati yang menyebabkan lama rawat inap di ICU.Kata kunci : Lama rawat inap ICU, koagulopati, kehamilan dengan COVID 19